Environmental and Social Responsibility Supplemented with Green Case Studies from the Side of the Tourism Service Providers - Horváth, Andrea; Jónás-Berki, Mónika (Turizam, 2018)
The environmental and social responsibility is a less researched area of tourism operators in Hungary. The tourism sector is one of the least regulated economic sectors in the global economy, but it can be seriously affected by ecological and social systems. The tourism supply requires a large amount of resources; therefore, a significant amount of waste is generated. By recognizing the effects of tourism, it is crucial for every society and economy to move forward to a more sustainable approach. At the social level, it can generate core processes, contribute to the population decrease in the area, but it can also cause social conflicts. The environmental and social sustainability requires a comprehensive approach and intervention to the sector as a whole. A wide range of stakeholders should be involved at all levels in order to create sustainability. The aim of the research is to explore the issue of environmental sustainability among tour operators by using Hungarian case studies.